2017
DOI: 10.1371/journal.pone.0174251
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of multiple obesity indices for cardiovascular disease risk classification in South Asian adults: The CARRS Study

Abstract: BackgroundWe comparatively assessed the performance of six simple obesity indices to identify adults with cardiovascular disease (CVD) risk factors in a diverse and contemporary South Asian population.Methods8,892 participants aged 20–60 years in 2010–2011 were analyzed. Six obesity indices were examined: body mass index (BMI), waist circumference (WC), waist-height ratio (WHtR), waist-hip ratio (WHR), log of the sum of triceps and subscapular skin fold thickness (LTS), and percent body fat derived from bioele… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
32
1
3

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(40 citation statements)
references
References 35 publications
(34 reference statements)
4
32
1
3
Order By: Relevance
“…Despite this gap, a recent investigation observed that WSR is more strongly associated with hypertension than BMI, WC, and WHR in men and women from India and Pakistan [8]. In line with this, a previous research analyzing a large sample of Chinese men and women ( n = 2895; 25–74 years old) observed that WSR was the best index in predicting elevated systolic and diastolic BP in women when compared to BMI, WC, and WHR (WSR likelihood ratios in that study were 3.05 and 3.38 for systolic and diastolic BP, respectively) [10].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Despite this gap, a recent investigation observed that WSR is more strongly associated with hypertension than BMI, WC, and WHR in men and women from India and Pakistan [8]. In line with this, a previous research analyzing a large sample of Chinese men and women ( n = 2895; 25–74 years old) observed that WSR was the best index in predicting elevated systolic and diastolic BP in women when compared to BMI, WC, and WHR (WSR likelihood ratios in that study were 3.05 and 3.38 for systolic and diastolic BP, respectively) [10].…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, excess body weight caused by genetic and/or sedentarism and bad nutrition is commonly associated with the incidence of hypertension [1]. Noteworthy, several adiposity indices, such as body mass index (BMI), waist circumference (WC), conicity index (C), and waist-to-hip-ratio (WHR), have been extensively applied to assess cardiovascular risk factors among adults and elderly people [68]. In fact, studies have shown that those indices, particularly when WC is accounted for, are good predictors of hypertension [7, 8].…”
Section: Introductionmentioning
confidence: 99%
“…It is reported that this index gives particularly a notion about being overweight or obese among adults. However, there are many studies performed on adults that do not recommend BMI, instead propose other obesity indices for various purposes such as prediction of hypertension, cardiovascular disease risk classification or as discriminators of in the diagnosis of metabolic syndrome (Chua, Zalilah, Haemamalar, Norhasmah, & Geeta, 2017;Patel et al, 2017;Motamed et al, 2016;Motamed et al, 2017;Fan et al, 2016). Besides, a very recent study has reported that LDL-cholesterol, which is found to be elevated in obese individuals and also known as a risk factor for CVDs is not associated with BMI or waist circumference (Oda, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…Obesity indices have recently been a point of interest during the investigation of obesity, risk factors of obesity and obesity-related diseases such as metabolic syndrome, coronary artery disease, acute myocardial infarction and type 2 diabetes (Motamed et al, 2016;Motamed et al, 2017;Mondal & Mishra, 2017;Chua, Zalilah, Haemamalar, Norhasmah, & Geeta, 2017;Patel et al, 2017;Abulmeaty et al, 2017;Tsioufis et al, 2016;Jelavic, Babic & Pintaric, 2017;Liu, Ma, Lou & Zhu, 2016;Tao et al, 2016;Oguoma et al, 2016). So far a great number of studies have been performed on adults with different obesity grades, however research performed on pediatric population ) is scarce.…”
Section: Scope Of the Problemmentioning
confidence: 99%
See 1 more Smart Citation